The Christmas escape - Morgan, Sarah, 1948- (HQN, 2021)
"It was supposed to be Christy Sullivan's perfect Christmas getaway--a trip to Lapland with her family and best friend, Alix. But facing a make-or-break marriage crisis, Christy desperately needs time alone with her husband. Her solution? Alix can take Christy's little daughter to Lapland, and they will reunite there for Christmas Day. It's a big ask, but what else are friends for? There's nothing Alix won't do for Christy. But Christy's request to save Christmas is giving Alix sleepless nights. She knows something is wrong, but for the first time ever, Christy isn't talking. And even the Arctic temperatures in Lapland aren't enough to dampen the seriously inconvenient sizzle Alix is developing for Zac, a fellow guest and nemesis from her past. As secrets unravel and unexpected romance shines under the northern lights, can Christy and Alix's Christmas escape give them the courage to fight for the relationships they really want, and save the precious gift of each other's friendship?"--Book jacket.